Indonesia Crowdfunding Cooperatives (IC Coop): Inisiatif Integrasi Koperasi Bagi Pemulihan Ekonomi Nasional Secara Kolektif - Herawan, Jonathan Ersten; Susilo, Yuvensius Sri; Putranto, Laurensius Farel Dwi (Jurnal Maksipreneur, 2024)
One of the characteristics of the Indonesian nation is cooperation one of the differentiating factors that play an important role in the resilience of the national economy which is based on unity and diversity (Pancasila) to continue to grow. Economic recovery and an increase in the growth trend of cooperatives are signals and momentum for utilizing cooperatives as an alternative route for national economic recovery. The background of this paper aims to map the potential and obstacles faced by cooperatives to support national economic recovery and offer applicable recommendations for policymakers in economic recovery schemes that are more inclusive and adaptive to dynamics using qualitative descriptive methods and literature study. This research provides recommendations on an applied basis, which is the establishment of a centralized authority that handles cooperatives in an integrated cooperative called Indonesia Crowdfunding Cooperatives (IC Coop) to integrate the development of the national cooperative system starting from the licensing (legal), operation (operation), supervision (supervision) stages, mentoring, and upgrading cooperatives in supporting the national economy based on Sapta Tantra by becoming a cooperative as an integrated community for an integrated economy.